Fibrin biopolymer as scaffold candidate to treat bone defects in rats - Cassaro, Claudia Vilalva [UNESP]; Justulin, Luis Antonio [UNESP]; De Lima, Patrícia Rodrigues [UNESP]; De Assis Golim, Marjorie [UNESP]; Biscola, Natália Perussi [UNESP]; De Castro, Mateus Vidigal; De Oliveira, Alexandre Leite Rodrigues; Doiche, Danuta Pulz [UNESP]; Pereira, Elenize Jamas [UNESP]; Ferreira, Rui Seabra [UNESP]; Barraviera, Benedito [UNESP] (FapUNIFESP (SciELO), 2019)
Background: Bone tissue repair remains a challenge in tissue engineering. Currently, new materials are being applied and often integrated with live cells and biological scaffolds. The fibrin biopolymer (FBP) proposed in this study has hemostatic, sealant, adhesive, scaffolding and drug-delivery properties. The regenerative potential of an association of FBP, biphasic calcium phosphate (BCP) and mesenchymal stem cells (MSCs) was evaluated in defects of rat femurs. Methods: Adult male Wistar rats were submitted to a 5-mm defect in the femur. This was filled with the following materials and/or associations: BPC; FBP and BCP; FBP and MSCs; and BCP, FBP and MSCs. Bone defect without filling was defined as the control group. Thirty and sixty days after the procedure, animals were euthanatized and subjected to computed tomography, scanning electron microscopy and qualitative and quantitative histological analysis. Results: It was shown that FBP is a suitable scaffold for bone defects due to the formation of a stable clot that facilitates the handling and optimizes the surgical procedures, allowing also cell adhesion and proliferation. The association between the materials was biocompatible. Progressive deposition of bone matrix was higher in the group treated with FBP and MSCs. Differentiation of mesenchymal stem cells into osteogenic lineage was not necessary to stimulate bone formation. Conclusions: FBP proved to be an excellent scaffold candidate for bone repair therapies due to application ease and biocompatibility with synthetic calcium-based materials. The satisfactory results obtained by the association of FBP with MSCs may provide a more effective and less costly new approach for bone tissue engineering.
Keywords: Biomaterials; Biphasic calcium; Bone regeneration; Fibrin biopolymer; Fibrin sealant; Mesenchymal stem cells; Phosphate